Adolescent and Young Adult (AYA) Oncology in the United States. Issue 3 (April 2015) - Shaw, Peter H.; Reed, Damon R.; Yeager, Nicholas; Zebrack, Bradley; Castellino, Sharon M.; Bleyer, Archie
<x xml:space="preserve">Abstract</x> Over the last 30 years, it has become apparent that oncology patients ages 15 to 39 have not reaped the same rewards of improved survival that we have seen in younger and older patients. As a result, in 2006 the Adolescent and Young Adult (AYA) Oncology Progress Review Group convened and examined the factors that impact the care of the 70, 000 new cases per year (approximately 7% of all new cases) in the United States and published their findings. The reasons for inferior survival gains are of course multiple and include the settings in which patients are cared for, clinical trial enrollment, insurance coverage, varied treatment of sarcomas, varied treatment of acute lymphoblastic leukemia, the psychosocial impact of cancer and cancer survivorship. A new area of a yet-to-be completely defined subspecialty was born out of this meeting: AYA oncology. As a medical community we realized that these patients do not fit neatly into the pediatric nor adult world and, therefore, require a unique approach which many individuals, oncology centers, advocacy groups, and cooperative trial groups have started to address. This group of dedicated providers and advocates has made strides but there is still much work to be done on the local, national, and international level to make up for shortcomings in the medical system and improve outcomes. We review key components of AYA cancer care in 2015 that all providers should be aware of, how far we have come, where this movement is headed, and the obstacles that continue to stand in the way of better cure rates and quality of life after cure for this unique group of patients. Like an adolescent maturing into adulthood, this movement has learned from the past and is focused on moving into the future to achieve its goals.